Analisis Wacana Kritis Program Blak-Blakan Edisi Keempat Jawa Pos Radar Semeru TV - Abdul Choliq; Muhammad Sidkin Ali (Program Studi Komunikasi Penyiaran Islam Universitas Sains Al-Qur'an Jawa Tengah di Wonosobo, 2023)
The massive development of information technology causes print media to adapt quickly and precisely, one of which is through convergence. The Daily Newspaper Jawa Pos Radar Semeru has converged with social media to maintain its existence in the era of digital disruption. One of the social media shows that are widely appreciated by the public is the flagship program Blak-Blakan on the Radar Semeru TV youtube channel which airs every Wednesday night. In the fourth edition of the Blak-Blakan program with the topic